Beyond Social Presence: Facelessness and the Ethics of Asynchronous Online Education - Rose, Ellen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
In this position paper, I argue that a focus on achieving and increasing social presence in online courses tends to derail a consideration of the ethical implications and dimensions of the essential facelessness of asynchronous education. Drawing upon the work of Emmanuel Levinas and Nel Noddings, who contended that the face is the basis of caring, ethical relations, I explore what it means for human relations, education, and society in general that learners increasingly come face-to-face with screens rather than with embodied, different others.